Research progress of hydrogels as delivery systems and scaffolds in the treatment of secondary spinal cord injury - Peng, Haichuan; Liu, Yongkang; Xiao, Fengfeng; Zhang, Limei; Li, Wenting; Wang, Binghan; Weng, Zhijian; Liu, Yu; Chen, Gang (Frontiers in Bioengineering and Biotechnology, 2023)
Secondary spinal cord injury (SSCI) is the second stage of spinal cord injury (SCI) and involves vasculature derangement, immune response, inflammatory response, and glial scar formation. Bioactive additives, such as drugs and cells, have been widely used to inhibit the progression of SSCI. However, the delivery and long-term retention of these additives remain a problem to be solved. In recent years, hydrogels have attracted much attention as a popular delivery system for loading cells and drugs for SSCI therapy. After implantation into the site of SCI, hydrogels can deliver bioactive additives in situ and induce the unidirectional growth of nerve cells as scaffolds. In addition, physical and chemical methods can endow hydrogels with new functions. In this review, we summarize the current state of various hydrogel delivery systems for SSCI treatment. Moreover, functional modifications of these hydrogels for better therapeutic effects are also discussed to provide a comprehensive insight into the application of hydrogels in the treatment of SSCI.